MSAP-based analysis of DNA methylation diversity in tobacco exposed to different environments and at different development phases. (October 2015) - Zhang, P.Y.; Wang, J.G.; Geng, Y.P.; Dai, J.R.; Zhong, Y.; Chen, Z.Z.; Zhu, K.; Wang, X.Z.; Chen, S.Y.
Abstract: The DNA methylation phenomenon, which plays an important role in the regulation of gene expression, exists in most eukaryotes. In this study, we employed methylation-sensitive amplification polymorphism (MSAP) technology to investigate the extent and patterns of methylation in tobacco planted in five different areas of Dali County, Yunnan Province. All of the samples were collected during the vegetative and reproductive growth phases. The data obtained from the MSAP analysis showed that full-methylation and non-methylation modifications were predominant and that the hemi-methylation modification ratio was markedly lower. The PCA and UPGMA analysis results indicated that the samples collected from different areas during the vegetative and reproductive growth phases exhibit certain differences: development had a more significant impact on the methylation diversity than environmental factors, although the samples collected at the same growth stages showed that the geographical environment may also affect the methylation status. The sequencing and BLASTn analyses indicated that most of the bands that showed significant polymorphisms are highly homologous to some methylation-sensitive-related sequences discovered in tobacco or other plant species and that many of these sequences are closely related to growth regulation or environmental factors. Highlights: We demonstrated the methylation status of tobacco collected from different environments and development phases. The relationship among environment, development and methylation status was discussed according to PCA and UPGMA analysis. The gel bands, which showed notable polymorphism, were recycled and cloned for sequencing for further analysis.